Vzájemný vztah občanské společnosti a státu v kontinuálně evropském typu právní kultury - Pinz, Jan (Univerzita Pardubice, 1998)
Every step in the evolutionary ladder of social organisation is considered to be a form of civilisation, i. e. for social formation with a specifable developmental of the moral culture. Because moral civilisation is in reality to the phenomenon of law it therefore corresponds in parallel to a specific type of civilisation is a state civilisation as well. Human society, organised into the form of a state, became a societal state and has been integrated with the state for centuries. In the 18th century human society was broken into political and civilian societies, which differentiated between the state and society on the whole. The equivalence of public sphere was found in the political society and was not identical to the state. The private sphere as opposed to the state finds its expression in the citizen's society. The duality if citizen's society and state is typical of the modern rule of law. The task of citizen's society is to place as effective obstacles as possible againts any illicit and wrongful of the powers of law into the life of citizen's.
Keywords: občanská společnost; stát; civilizace; právní kultura